PENGARUH MODEL COOPERATIVE SNOWBALL THROWING BERBASIS WORDWALL TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA - Nurul Hasinah; Moh. Rudini; Mustakim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve the critical thinking skills of fifth-grade students of SDN 6 Tambun in the subject of Natural Sciences through the application of the Snowball Throwing Cooperative learning model based on Word Wall media. This study uses a quantitative approach with a True Experimental Design in the form of pretest-posttest only. The subjects of the study consisted of 13 students who were given treatment during three meetings with different Natural Sciences topics. The instruments used included a critical thinking skills test (based on the FRISCO indicator), observation sheets, and Student Worksheets (LKPD). The results showed an increase in the average score from the pretest of 76.62 to 87.08 in the posttest. The results of the Paired Sample T-Test showed a significant value of 0.000 <0.05, which means there is a significant effect of the learning model on improving students' critical thinking skills. Thus, the application of the Snowball Throwing Cooperative model based on Word Wall media is proven to be effective in improving students' critical thinking skills in Natural Sciences learning.